PENGARUH PEMBERDAYAAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI DAN KOMITMEN ORGANISASIONAL ( Studi pada Kecamatan Kragan Kabupaten Rembang ) - 11.42.02.0127, Mashadi (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to analyze the effects of empowerment and job characteristics on the job performance through motivation and organizational commitment (A Study in Distric Kragan of Rembang Regency).The population in this study is the all civil service in the area of distric Kragan amount to 174 people. This study use proportional sampling, where samples are selected based on the particular purpose. As for the acceptance criteria for the samples are limited only for employee whoâs with minimum service of 5 years . Thus reduced the samples into 115 people.This study using statistical tests that include validity test with factor analysis, reliability test using Cronbachs alpha, double regression analysis, and significance test using the coefficient of determination to prove the validity of hypothesis and for mediation tests. The results of this study correctly proved that modelâs ability to explain correctly , the variable of empowerment, job characteristic, motivation and organizational commitmentâs influence to job performance is amounted 96,3% . Whereas the otherâs is 3,7% as explained by variables outside the data-model. Mediating effect test proved that the effect of empowerment and job characteristic to job performance is not mediated by motivation and organizational commitment Keywords : empowerment, job characteristics, motivation, organizational commitment and job performance